Aplikasi Ruangan Maya Berbasis Android OS pada Headset Virtual Reality Oculus Quest 2 - Christopher Santoso, Alvin; Santoso, Petrus (Jurnal FORTECH, 2022)
Metaverse and VR (virtual reality) technology brings a lot of benefits to some sectors of life, especially education because VR technology makes it possible for users to be placed in a simulation of a certain scenario or situation which helps with the user’s learning experience. The development of computer technology where computer components are much smaller in size, have better computational capacity, and low cost has made VR technology more available and offers more and more opportunities as computer technology develops even further. In order to take advantage of the increasing opportunity, a virtual room application based on Android OS for Oculus Quest 2 is developed in order to learn about virtual reality development workflow on a VR headset using Unity game engine. The features implemented in the virtual room app are locomotion control by teleportation and continuous movement, rotation by snap turning, interactable objects such as a mirror, grabbable objects which the user can hold in the virtual room, and sockets to place digital objects in the virtual room.